CES 2019
DOI: 10.15179/ces.21.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Economic and Political Events on Stock Returns: Event Study of the Agrokor Case in Croatia

Abstract: Major events in Croatia regarding economy and politics in the last three years have been related to the Agrokor concern. Agrokor is one of the biggest companies/ concerns in Croatia and Southeastern Europe. Since some of Agrokor's stocks are listed on the Croatian stock market, the economic and political events regarding Agrokor have affected the stock market as well to an extent. In this study we observe the effects of several economic and political events on stock returns on the Zagreb Stock Exchange, by div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…The stock returns that reacted the most (when observing Figures 2-4) are wig, budapest, sbi, and px, which is in line with findings in [97,98], where these markets were found to be most responsive to systematic shocks, as well as bad news reactions to the Brexit vote in [35]. The reaction of sbi and wig is in line with [72] as well, where negative shocks in economic uncertainties spilled over to those two returns in a great manner (i.e., the return series of sbi and wig were found to be net receivers of outside shocks). Furthermore, the least reactions found regarding returns on pfts, birs, and sax are in line with [97], in which the author found that systematic outside-country shocks had the least effects on the mentioned markets, and as [72] found that uncertainties, especially for the pfts series, were found not to affect certain country index returns in a significant manner.…”
Section: Main Analysis: Esm Estimation Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The stock returns that reacted the most (when observing Figures 2-4) are wig, budapest, sbi, and px, which is in line with findings in [97,98], where these markets were found to be most responsive to systematic shocks, as well as bad news reactions to the Brexit vote in [35]. The reaction of sbi and wig is in line with [72] as well, where negative shocks in economic uncertainties spilled over to those two returns in a great manner (i.e., the return series of sbi and wig were found to be net receivers of outside shocks). Furthermore, the least reactions found regarding returns on pfts, birs, and sax are in line with [97], in which the author found that systematic outside-country shocks had the least effects on the mentioned markets, and as [72] found that uncertainties, especially for the pfts series, were found not to affect certain country index returns in a significant manner.…”
Section: Main Analysis: Esm Estimation Resultssupporting
confidence: 83%
“…The reaction of sbi and wig is in line with [72] as well, where negative shocks in economic uncertainties spilled over to those two returns in a great manner (i.e., the return series of sbi and wig were found to be net receivers of outside shocks). Furthermore, the least reactions found regarding returns on pfts, birs, and sax are in line with [97], in which the author found that systematic outside-country shocks had the least effects on the mentioned markets, and as [72] found that uncertainties, especially for the pfts series, were found not to affect certain country index returns in a significant manner. Some of the reasoning on why certain index returns reacted so strongly and some had almost no reaction at all to certain events is as follows.…”
Section: Main Analysis: Esm Estimation Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…In the Hungarian case, the RV and GSV variables were, for the majority of the time, net givers of shocks. In Croatia, the financial crisis of 2008 shows that the GSV was the net emitter of shocks (similar was true for 2017, when a local crisis caused by the Agrokor concern was happening, for details please see Škrinjarić (2018b) and Škrinjarić and Orlović (2019)). In the rest of the observed period, there was an interchangeability of net emitters and receivers of shocks.…”
Section: Spillover Indices Resultsmentioning
confidence: 74%
“…Results confirmed that an increase or decrease in a dividend significantly affected the stock price in the same direction, while a dividend retention had no effect on the stock price. Škrinjarić and Orlović (2019) applied the event study methodology in order to test whether political events regarding the Agrokor group of companies affected stock prices. Their results indicate that stocks which belonged to Agrokor suffered from lowering returns, while other liquid stocks on the Zagreb Stock Exchange were not affected.…”
Section: Literature Reviewmentioning
confidence: 99%